Development AES Algorithm to Encryption Images and Sounds Files - Mohammed Al-Zubaidy (Al-Rafidain Journal of Computer Sciences and Mathematics, 2012)
In this research, the Advanced Encryption Standard (AES) algorithm was developed, the AES is used for encryption and decryption the images and sounds files by expanding the block size of data to reach the maximum size of 512 bit instead 128 bit/cycle, by using the Thread API techniques, which is a break off CPU working for increasing times taken the inline encrypt or decrypt operations. The data entranced from the file by size 512 bits per cycle, is converted to one dimension matrix by block size which is 2048 bit. The method considered 4-lines using 4 AES, which in every line, one AES is working in a distinct system. Transmission and reception of encoded files could be performed by using Email programs provided that the sent file does not include the encoding key for the purpose of protecting encoded files against unauthorized access. In addition to the use of the histogram in this research by comparing the block size of images or sounds files through the encrypting or decrypting system by scanning bit to bit operations. The implement algorithm with a sample of histogram was used to ensure that the data is not changed throughout this study.